Ensaio clínico duplo-cego controlado e randômico, comparando a eficácia da Clofazimina com a Cloroquina, no tratamento das lesões cutâneas do Lúpus Eritematoso Sistêmico - Bezerra, Elaine Lira Medeiros (2007)
PURPOSE: To evaluate the capacity of clofazimine (CFZ) to control cutaneous activity of systemic lupus erythematosus (SLE), compared with chloroquine diphosphate (CDP). METHODS: A prospective, randomized, controlled, double blind clinical trial was carried out in thirty-three patients with SLE and cutaneous lesions (malar rash and/or discoid lupus and/or subacute cutaneous lupus), after approval by the respective Ethics Committee. Sixteen patients received clofazimine - 100mg/day (CFZ group) and 17 received chloroquine diphosphate - 250mg/day (CDP group), during six months. Both groups applied broad-spectrum sunscreens twice a day. The dose of prednisone was kept stable during the study. Cutaneous lesions were evaluated by 2 blinded observers and photographed at baseline and at months 1, 2, 4 and 6. RESULTS: Thirty-three patients began and 27 completed the 6 months of treatment. The groups were homogeneous and comparable in terms of demographic and clinical characteristics. Five CFZ-patients and one CDP-patients dropped out due to severe flare of disease requiring other treatment. At the end of the study, 12 CFZ-patients (75%) and 14 CDP-patients (82,4%) presented complete or near-complete remission of skin lesions; intention-to-treat analysis showed no significant difference in the response rates between groups. Side effects in both groups were frequent, but patients didn t have to discontinue the drugs. CONCLUSIONS: Clofazimine and chloroquine were effective in controlling cutaneous lesions in SLE patients